Identifikasi potensi situs hunian gua di karst Zona Rembang bagian barat - Hari Wibowo; Ahmad Surya Ramadhan; Muhammad Wishnu Wibisono; Rakhmat Dwi Putra (Berkala Arkeologi, 2022)
The karst area in Pati and Grobogan is the western segment of the Rembang Zone on the northern karst of Java which has not been studied intensively by the archaeologists. This article describes the potential cave occupation sites in the karst area of Pati and Grobogan. Data for this article was collected through field surveys and analysed using a qualitative and quantitative methods. The qualitative method served as data filters before the quantitative analysis. The quantitative method was applied to rank the observed objects based on the variables of accessibility, morphological, and archaeological data. The results demonstrate that the karst segment in Pati, especially in the Sukolilo subdistrict, has a higher potential than the karst area in Rembang and Grobogan. Out of the 29 caves surveyed, five are archaeologically potential as prehistoric settlements. Of the five caves, only one cave is ranked as having high potential and the rest is ranked as medium potential. Regarding their location, the five caves with archaeological potential are scattered along the north side of the karst hills of the Pati Regency area.